ЗМІСТ СФОРМОВАНОСТІ ГОТОВНОСТІ СТУДЕНТІВ ПЕДВУЗІВ ДО ДІАЛОГІЧНОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2004)
The article deals with the problem of content of students' readiness to the using of dialogue in educational process. Researching results show its influence on the effectiveness of dialogue education.